Cost-effective production of dextran using Saccharum officinarum juice (SOJ) as a potential feedstock: downstream processing and characterization - Rahman, Sameeha Syed Abdul; Venkatachalam, Ponnusami; Karuppiah, Sugumaran (Biomass conversion and biorefinery, 2022)
Dextrans are exo-polysaccharides prominently used as biomaterial on the grounds of their biodegradability and biocompatibility characteristics. There is an increasing interest and need to identify alternative cost-effective and renewable carbon source for dextran to reduce the production cost and to improve the overall economy of dextran production. In this work, dextran was produced using Saccharum officinarum juice (SOJ) as a low-carbon source by Leuconostoc mesenteroides MTCC 7337. The suitable condition/parameter for the production of dextran was found to be medium pH, 7; shaking speed, 150 rpm; inoculum size, 5% v/v; and nitrogen source, yeast extract. The different downstream factors including screening of solvent, supernatant to solvent ratio and precipitation time on the recovery of dextran, were studied. The organic solvent, ethanol with volume ratio of 1:4 (supernatant to solvent ratio), and precipitation time of 16 h were selected based on the maximum recovery of dextran from SOJ medium. The purified dextran was characterized by proton nuclear magnetic resonance spectroscopy ( 1 H-NMR), Fourier transform infrared spectroscopy (FTIR), and thermogravimetric analysis (TGA) analysis. The results of rheological studies indicate that dextran solution behaves like a pseudoplastic fluid at higher concentrations of dextran solution. Based on the results, it was found that SOJ could be used as an alternate substrate for the production of dextran.